2005
DOI: 10.1111/j.1540-4560.2005.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative Action and Job Satisfaction: Understanding Underlying Processes

Abstract: In the present article, we examine the relationship between perceptions of affirmative action and the satisfaction of racial and ethnic minority faculty members. We develop a conceptual model of factors that mediate the impact of affirmative action on the satisfaction of faculty of color, and investigate this model based on survey responses of 84 African-American, 48 Latina/o, and 59 Asian faculty. Analyses showed that the satisfaction of faculty of color is significantly related to how affirmative action is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Substantial effects remained even in the presence of controls for job-related variables and disciplinary characteristics. These findings support past research, which has found pronounced gender and racial/ethnic differences in perceptions of equitable treatment towards women and faculty of color (Aguirre 1993(Aguirre , 2000Bronstein and Farnsworth 1998;Hagedorn 1996;Marcus 1998;Niemann and Dovidio 2005;Ponjuan 2005;Peterson et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Substantial effects remained even in the presence of controls for job-related variables and disciplinary characteristics. These findings support past research, which has found pronounced gender and racial/ethnic differences in perceptions of equitable treatment towards women and faculty of color (Aguirre 1993(Aguirre , 2000Bronstein and Farnsworth 1998;Hagedorn 1996;Marcus 1998;Niemann and Dovidio 2005;Ponjuan 2005;Peterson et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…The value of mentoring programs to minority and female scholars has received increasing attention in recent higher education literature (see for example Bensimon, Ward, and Sanders, 2000;Niemann and Dovidio, 2005;Ragins, 1995;Turner, Myers, Samuel, and Creswell, 1999). Department chairs play an instrumental role as mentors in guiding new faculty in teaching, research, and institutional citizenship related to successful attainment of tenure (Bensimon, Ward, and Sanders, 2000).…”
Section: Model Reciprocal Empowerment Through Mentorshipmentioning
confidence: 97%
“…A study of 231 minority faculty members of the American Psychological Association indicates that when affirmative action programs are perceived as nonvoluntary and imposed, these faculty members experienced a less positive departmental climate and also experienced greater self-doubt which undermined job satisfaction (Niemann and Dovidio, 2005). By contrast, when such programs are seen as voluntary in terms of sincere and willing departmental efforts to recruit minorities and females in support of institutional affirmative action policies, minority faculty experienced a more positive departmental climate and also experienced less self-doubt (Niemann and Dovidio, 2005). These results suggest that both institutional and departmental leadership are critical in articulating the larger benefits of affirmative action for the entire organization to mitigate the effects of intergroup competition.…”
Section: Create Formal Programs That Enhance Intergroup Contact and Dmentioning
confidence: 98%
See 1 more Smart Citation
“…Members of the dominant group in higher education continue to resist change by using the power they hold in the organizational culture of higher education and the power of the courts when they challenge the constitutionality of diversity initiatives such as affirmative action, which is itself a mechanism reflecting the a co-optation strategy for organizational development (Aguirre and Martinez, 2003a;Garcia, 2000;Niemann and Dovidio, 2005;Padilla and Martinez, 2005).…”
Section: Co-optation Versus Transformation Strategiesmentioning
confidence: 98%